University extension and Popular Education: the perspective of Popular Extension - Silveira Fraga, Lais (2024)
In a context of curricularization of extension, implementation of the Quota Law for Higher Education and the enlargement of the concept of university extension, this article aims to reflect on the perspective of Popular Extension in the current conjuncture, through the analysis of the texts of its main author José Francisco de Melo Neto from the Federal University of Paraíba (UFPB). The question we seek to explore is: what are the particularities of the conception of Popular Extension, its main characteristics and contributions to the field of University Extension in the current conjuncture? Additionally, we aim to reflect on the limits and possibilities of this perspective from an intersectional perspective. There is a particular interest in understanding the theoretical and methodological foundations of this extensionist perspective in dialogue with its formulation context, and how it unfolds through new questions and struggles presented by the current context.